Evaluate the limit $\displaystyle \lim_{n\rightarrow \infty}\frac{1}{\sqrt{n}}\left(1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\ldots+\frac{1}{\sqrt{n}}\right)$, without using a Riemann sum

$\bf{My\; Try:}$ Using the graph of $\displaystyle f(x) = \frac{1}{\sqrt{x}}\;,$ we get

$$\int_{1}^{n+1}\frac{1}{\sqrt{x}}dx <\left(1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\ldots+\frac{1}{\sqrt{n}}\right)<1+\int_{1}^{n}\frac{1}{\sqrt{x}}dx$$

So we get $$2\sqrt{n+1}-2<\left(1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\ldots+\frac{1}{\sqrt{n}}\right)<2\sqrt{n}-1$$

So $$\lim_{n\rightarrow \infty}\frac{2\sqrt{n+1}-2}{\sqrt{n}}=2<\lim_{n\rightarrow \infty}\frac{1}{\sqrt{n}}\left(1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\ldots+\frac{1}{\sqrt{n}}\right)<\lim_{n\rightarrow \infty}\frac{2\sqrt{n}-1}{\sqrt{n}} = 2$$

So using the Sandwich Theorem, we get $\displaystyle \lim_{n\rightarrow \infty}\frac{1}{\sqrt{n}}\left(1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\ldots+\frac{1}{\sqrt{n}}\right)=2$

My question is can we solve it by using any other method? If yes then please explain it here.


3 Answers 3


By Cesaro-Stolz

$$\ldots = \lim_{n \to \infty} \frac{\sum_{k=1}^{n+1} \frac{1}{\sqrt{k}}- \sum_{k=1}^{n} \frac{1}{\sqrt{k}} }{\sqrt{n+1}-\sqrt{n}} = \lim_{n \to \infty} \frac{\frac{1}{\sqrt{n+1}}}{\sqrt{n+1}-\sqrt{n}} = \lim_{n \to \infty} \frac{\frac{1}{\sqrt{n+1}}(\sqrt{n+1} + \sqrt{n})}{n+1 - n} = 2 $$

Also, there is another approach using the squeeze theorem that parallels your argument without appealing to the integral.

Since $\sqrt{k} + \sqrt{k-1} < 2\sqrt{k} < \sqrt{k} + \sqrt{k+1}$ we find the bounds

$$2(\sqrt{k+1} - \sqrt{k})=\frac{2}{\sqrt{k+1} + \sqrt{k}} \leqslant \frac{1}{\sqrt{k}} \leqslant \frac{2}{\sqrt{k} + \sqrt{k-1}} = 2(\sqrt{k} - \sqrt{k-1}).$$

As sums of the LHS and RHS are telescoping, we have

$$2(\sqrt{n+1} - 1) \leqslant \sum_{k=1}^n \frac{1}{\sqrt{k}} \leqslant 2\sqrt{n},$$


$$2(\sqrt{1+1/n} - 1/\sqrt{n}) \leqslant \frac{1}{\sqrt{n}}\sum_{k=1}^n \frac{1}{\sqrt{k}} \leqslant 2.$$

Now apply the squeeze theorem.

  • 3
    $\begingroup$ For those too lazy to look it up: If $a_n$ and $b_n$ are strictly monotone divergent sequences, then $\lim_{n \to \infty} \dfrac{a_{n+1} - a_n}{b_{n+1} - b_n} = \lim_{n \to \infty} \dfrac{a_n}{b_n}$, assuming the former limit exists. Here we have $a_n = 1/\sqrt{1} + \dots + 1/\sqrt{n}$ and $b_n = \sqrt{n}$. $\endgroup$
    – MCT
    Jun 6, 2016 at 3:48
  • $\begingroup$ +1 This is precisely the way forward I would have taken with the restriction in the OP. -Mark $\endgroup$
    – Mark Viola
    Jun 6, 2016 at 4:13

Notice that:

$$\frac1{\sqrt n}\sum_{k=1}^n\frac1{\sqrt k}=\frac1n\sum_{k=1}^n(k/n)^{-1/2}$$

As $n\to\infty$, we get a Riemann sum:

$$\lim_{n\to\infty}\frac1n\sum_{k=1}^n(k/n)^{-1/2}=\int_0^1x^{-1/2}~\mathrm dx=2x^{1/2}\bigg|_0^1=2$$


From the Euler-Maclaurin Summation Formula, we have

$$\begin{align} \frac{1}{\sqrt{n}}\sum_{k=1}^n\frac{1}{\sqrt{k}}&=\frac{1}{\sqrt{n}}\left(1+\int_1^n \frac{1}{\sqrt{x}}\,dx+\frac12\left(\frac{1}{n^{1/2}}-1\right)+O(1)\right)\\\\ &=2+O\left(\frac{1}{n^{1/2}}\right)\\\\ &\to 2\,\,\text{as}\,\,n\to \infty \end{align}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.